The phylogeny and global biogeography of Primulaceae based on high-throughput DNA sequence data - Larson, Drew; Chanderbali, Andre; Maurin, Olivier; Goncalves, Deise; Dick, Christopher; Soltis, Douglas; Soltis, Pamela; Fritsch, Peter; Clarkson, James; Grall, Aurélie; Davies, Nina; Larridon, Isabel; et al. (Dryad, 2022)
The angiosperm family Primulaceae is morphologically diverse and
distributed nearly worldwide. However, phylogenetic uncertainty has
limited the ability to identify major morphological and biogeographic
transitions. We used target capture sequencing with the Angiosperms353 kit
for over 300 species across Ericales, tree-based sequence curation, and
multiple phylogenetic approaches to investigate the phylogenetics of the
major clades of Primulaceae and their relationship to other Ericales. The
study included 150 samples of Primulaceae comprising nearly all recognized
genera of the family, with a particular focus on the most diverse
subfamily, Myrsinoideae, for which previous phylogenetic knowledge was
poor. We used fossil and secondary calibrations to generate dated
phylogenetic trees and conducted broad-scale biogeographic analyses as
well as ancestral state reconstructions of plant habit.
Keywords: FOS: Biological sciences